An introduction to copulas - Nelsen, Roger B. (Lecture notes in statistics, 1999)
Discussions of the fundamental properties of copulas and some of their primary applications are the main focus of this text. The applications include the study of dependence and measures of association, and the construction of families of bivariate distributions.